2013
DOI: 10.5897/ajps2013.1107
|View full text |Cite
|
Sign up to set email alerts
|

Species composition, diversity and distribution in a disturbed Takamanda Rainforest, South West, Cameroon

Abstract: This study assessed the diversity and distribution of trees and shrubs in a 16 ha disturbed plot in the Takamanda Rainforest. Linear transects (8) were laid in the field which radiated from the centre of the plot. The girth of the trees and shrubs were measured and species identified. A total of 99 species (72 trees and 27 shrubs) belonging to 87 genera and 34 families were recorded. Caesalpinaceae was the most represented tree family (9 species) while Rubiaceae was the most represented among shrubs (9 species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
(10 reference statements)
4
8
1
Order By: Relevance
“…The dominance value (Ds) recorded in present study (0.93) corresponds well with that recorded from other temperate forests, which ranged from 0.135-0.97 (Saha et al 2016;Ndah et al 2013). The Pielou evenness index (e) recorded from the present study (0.92) revealed that there is an even distribution of species within the forest.…”
Section: Floristic Diversity and Compositionsupporting
confidence: 87%
See 1 more Smart Citation
“…The dominance value (Ds) recorded in present study (0.93) corresponds well with that recorded from other temperate forests, which ranged from 0.135-0.97 (Saha et al 2016;Ndah et al 2013). The Pielou evenness index (e) recorded from the present study (0.92) revealed that there is an even distribution of species within the forest.…”
Section: Floristic Diversity and Compositionsupporting
confidence: 87%
“…In the present study, tree species diversity (H') in Fakim Wildlife Sanctuary was 3.90, which can be considered as high for temperate and tropical forests. For example, species diversity reported from mixed forest of Batuputih Nature Tourism Park, Indonesia was 3.31 (Arrijani and Rizki 2020), Takamanda rainforest in Southwest Cameroon was 3.87 (Ndah et al 2013) and temperate forest of Rudraprayag district of Garhwal Himalaya was 3.45 (Raturi 2012). The variation in species diversity with respect to environmental gradient acts as a major ecological investigation (Deb et al 2015;Erenso et al 2014;Gairola et al 2008), and various factors, such as climate, habitat, biotic interaction, edaphic, physiography, and productivity of the forest, play a major role in determining the species growth and production (Monson 2014;.…”
Section: Floristic Diversity and Compositionmentioning
confidence: 99%
“…The implication of this result is that, even though KNP got its legal status as a PA, its floral diversity degraded over time as a result of anthropogenic disturbances. The disturbance is possibly attributed to the exclusion of the local people from exercising their traditional rights (Nath et al, 2000) Bangladesh* 2.60 (Gopalakrishna, Kaonga, Somashekar, Suresh, & Suresh, 2015) India 1.99 (Panda, Mahapatra, Acharya, & Debata, 2013) India 2.94 (Thakur & Khare, 2006) India 2.28 (Parthasarathy & Sethi, 1997) India 3.58 (Tripathi et al, 2004) India 3.50 (Velho & Krishnadas, 2011) India 2.50 (Parthasarathy & Karthikeyan, 1997) India 4.27 (Kumar, Marcot, & Saxena, 2006) India 2.02 (Bhuyan, Khan, & Tripathi, 2003) India 2.41 (Aye, Pampasit, Umponstira, Thanacharoenchanaphas, & Sasaki, 2014) Myanmar 1.34 (Mishra & Garkoti, 2016) Nepal 5.61 (Hayat, Kudus, Faridah-Hanum, Noor, & Nazre, 2010) Malaysia 3.87 (Ndah, Andrew, & Bechem, 2013) Cameroon 2.91 (Nangendo, Stein, Gelens, De Gier, & Albricht, 2002) Uganda Evenness index 0.75-0.83 0.88 (Tripathi et al, 2004) India 0.60 (Gopalakrishna et al, 2015) India 0.99 (Panda et al, 2013) India 0.87 (Velho & Krishnadas, 2011) India 0.46 (Bhuyan et al, 2003) India 0.22 (Hayat et al, 2010) Malaysia 0.90 (Ndah et al, 2013) Cameroon Simpson index 0.10-0.20 0.06 (Tripathi et al, 2004) India 0.90 (Gopalakrishna et al, 2015) India 0.02 (Panda et al, 2013) India 0.06 (Bhuyan et al, 2003) India 0.84 (Aye et al, 2014) Myanmar 0.52 (Mishra & Garkoti, 2016) Nepal 0.15 (Hayat et al, 2010) Malaysia 0.03 (Ndah et al, 2013) Cameroon…”
Section: Importance Value Index (Ivi)mentioning
confidence: 99%
“…Though its mean species richness is far below other forest ecosystems both in Africa and across the Amazonia (Gentry, 1988;Phillips & Gentry, 1994;Richards, 1996;Ndah et al, 2013), it is similar with other freshwater swamp forests which are taken to be species poor as well (Scarano et al, 1997;Kurtz et al, 2013). While this could be generally attributed to the variations that exist in their abiotic environment, history and biogeography (Orians et al, 1996), it is equally as a result of the environmental constraints associated with the ecosystem.…”
Section: Discussionmentioning
confidence: 99%